2022
DOI: 10.1007/s10143-022-01840-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain infarction following meningioma surgery—incidence, risk factors, and impact on function, seizure risk, and patient-reported quality of life

Abstract: In this study, we seek to explore the incidence of and potential risk factors for postoperative infarctions after meningioma surgery, in addition to the possible association with new neurological deficits, seizures, and health-related quality of life (HRQoL). A single-center cohort study was conducted, where all patients operated for an intracranial meningioma at our institution between 2007 and 2020 were screened for inclusion. Clinical data were prospectively collected in a local tumor registry, and HRQoL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
2
5
0
Order By: Relevance
“…Regarding meningiomas, a review of 125 convexity meningioma resections showed that postoperative DWI obtained 24-48 h after surgery demonstrated restriction > 1 cm in 22% of the cases and symptomatic infarction in 11% [12]. Another study reported that early MRI performed within 72 h after meningioma resection detected peritumoral infarction in 34.9% of patients [13]. Our results are consistent with these studies.…”
Section: Role Of Early Postoperative Mri To Detect Ischemia After Men...supporting
confidence: 89%
“…Regarding meningiomas, a review of 125 convexity meningioma resections showed that postoperative DWI obtained 24-48 h after surgery demonstrated restriction > 1 cm in 22% of the cases and symptomatic infarction in 11% [12]. Another study reported that early MRI performed within 72 h after meningioma resection detected peritumoral infarction in 34.9% of patients [13]. Our results are consistent with these studies.…”
Section: Role Of Early Postoperative Mri To Detect Ischemia After Men...supporting
confidence: 89%
“…The intrinsic mechanisms of the epileptogenesis would be mainly mediated by the oxidative stress/free radicals formation (caused by extravascular leakage of blood components) and membrane ion imbalance (triggered by hypoxic–ischemic injury) [ 13 , 42 , 43 , 44 ]. Similar mechanisms can be hypothesized in case of the cortical injury resulting from the neurosurgical operation, where the microhemorrhages due to the cortical incision and the local ischemic damage resulting from the coagulation and/or the brain retraction (edema) can induce the aforementioned alterations, even though these modifications do not necessarily cause postoperative seizures [ 26 ]. The surgical incision of the brain can be considered per se as an epileptogenic stimulus.…”
Section: Discussionmentioning
confidence: 80%
“…These figures quite often are results from studies carried out in the past, the results of which are still cited in recent articles. As mentioned, specific studies in children are missing, with most of the current papers being focused on adults (often on the risks related to surgery for meningiomas) [ 24 , 25 , 26 ] or on the use of ASM prophylaxis [ 27 , 28 , 29 ]. The few studies on children usually comprise mixed series including either children with or without preoperative seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Vasospasms and blood vessel damage during surgery can cause local or extensive ischemia ( 13 , 20 ). In patients with malignant brain tumors, in addition to the tumor compression of peripheral blood vessels or tumor blood steal ( 21 , 22 ), cerebral ischemia may additionally be caused by tumor-induced inflammatory factors released into the periphery during tumor growth. However, the surgical procedure and inflammatory factors-related ischemia usually exist within or around the surgical field ( 23 ).…”
Section: Discussionmentioning
confidence: 99%